HUBUNGAN PENGETAHUAN IBU DENGAN KELENGKAPAN IMUNISASI LANJUTAN PADA BALITA DI WILAYAH KERJA PUSKESMAS JAILOLO - Widiatrilupi, Raden Maria Veronika; Kamarudin, Indira (NHM PRESS, 2024)
Background: Basic immunization is one of the important health interventions to prevent infectious diseases in infants. Mothers' knowledge about immunization plays a crucial role in determining the completeness of basic immunization in infants. In Jailolo Health Center, there is a concern that inadequate maternal knowledge can affect the completeness of immunization in infants. Objective: This study aims to analyze the relationship between maternal knowledge and the completeness of basic immunization in infants at Jailolo Health Center. Method: This study used a cross-sectional design involving 16 mothers who had babies at Jailolo Health Center as respondents. Data were collected through a questionnaire that measured the level of maternal knowledge about immunization and medical record examination to evaluate the completeness of infant immunization. Statistical tests were conducted to determine the relationship between maternal knowledge and the completeness of basic immunization, with a p-value <0.05 considered significant. Results: The results of the statistical test showed a p-value of 0.000, indicating that the null hypothesis (Ho) stating that there is no relationship between maternal knowledge and the completeness of basic immunization is rejected, while the alternative hypothesis (Ha) stating that there is a relationship is accepted. This indicates a significant relationship between maternal knowledge and the completeness of basic immunization in infants at Jailolo Health Center. Conclusion: Maternal knowledge about immunization is significantly related to the completeness of basic immunization in infants.